2016
DOI: 10.4018/ijissc.2016010104
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study of E-Participation Levels in Jordan

Abstract: The relationship between citizens and governments is the core of e-government. E-participation is one of the political dimensions of e-government which focuses on informing, consulting, involving, collaborating, and empowering citizens to take part of the decision making process. This study adopted a framework for the five levels of e-participation and tried to test such model empirically using 400 responses from Jordanians. The study tried to measure Jordanian perceptions towards e-participation initiatives a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
(44 reference statements)
0
2
0
1
Order By: Relevance
“…En donde top-down las acciones de participación son dadas por el gobierno y los ciudadanos son considerados como consumidores de estas acciones/políticas y por otro lado el enfoque bottom-up que son todas las acciones presentadas por los ciudadanos quienes son considerados productores de políticas en lugar de solo consumidores como en el nivel anterior. En la siguiente figura se pueden observar cómo funcionan los dos enfoques (Quintero, 2019;Raya Al-Dalou';Abu-shanab, 2013;Van Meerkerk, 2019). De acuerdo con la revisión sistemática de literatura llevada a cabo durante 2019, la mayoría de los estudios de e-Participación se centran en la consulta y la deliberación (Rose & Sanford, 2016;Sanford & Rose, 2007), es decir que, el punto central de e-Participación es el ciudadano, con el propósito de aumentar las capacidades de los ciudadanos para participar en la toma de decisiones (Serov & Leitner, 2017).…”
Section: Participaciónunclassified
“…En donde top-down las acciones de participación son dadas por el gobierno y los ciudadanos son considerados como consumidores de estas acciones/políticas y por otro lado el enfoque bottom-up que son todas las acciones presentadas por los ciudadanos quienes son considerados productores de políticas en lugar de solo consumidores como en el nivel anterior. En la siguiente figura se pueden observar cómo funcionan los dos enfoques (Quintero, 2019;Raya Al-Dalou';Abu-shanab, 2013;Van Meerkerk, 2019). De acuerdo con la revisión sistemática de literatura llevada a cabo durante 2019, la mayoría de los estudios de e-Participación se centran en la consulta y la deliberación (Rose & Sanford, 2016;Sanford & Rose, 2007), es decir que, el punto central de e-Participación es el ciudadano, con el propósito de aumentar las capacidades de los ciudadanos para participar en la toma de decisiones (Serov & Leitner, 2017).…”
Section: Participaciónunclassified
“…Jordan, like many other developing countries, introduced e-democracy initiatives such as "Bekhedmetkom" platform to enable citizens to participate in its democratic process. Research indicated that e-democracy initiatives are lagging in Jordan and face many challenges (Abu-Shanab et al, 2018;Abu-Shanab and Al-Dalou, 2016). Their findings emphasized the fact that Jordan is lagging behind in utilizing ICT for opening the e-participation channels.…”
Section: Introductionmentioning
confidence: 99%
“…The main definition and objective of e-government reported by many researchers is to provide an enhanced service utilizing ICT or the Internet [1]- [6]. Such definition lacks the overall perspective of e-government, where more focus towards e-democracy and public participation is embedded [7], [8]. On the other hand, the perspective of social contribution of e-government was introduced through the improvement of social life of citizens [9]- [12], and the digital divide [13].…”
Section: A E-government Conceptmentioning
confidence: 99%